STRATEGI PENGAMANAN WILAYAH PERAIRAN UNTUK MENINGKATKAN KINERJA KORPOLAIRUD BAHARKAM POLRI - Rustam Mansur; Zulkifli, Zulkifli; Agustinus Miranda W (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to determine the , safekeeping Strategy for the territorial waters to improve the performance of the Korpolairud Baharkam Polri at the at The Polri institution.. This research uses qualitative research methods. The qualitative analysis using SWOT, IFE & EFE and QSPM. As for the results of strategy analysis research through the input strategy stage with IFE, EFE, &CPM matching stage with TOWS and decision stage with QSPM, the strategy used from the QSPM results are alternative strategy of Strategy for Strengthening Facility & Infrastructure, Fleet & other sophisticated equipment. The Implication : Korpolairud to continue to develop facilities & infrastructure and adapt the fleet to digital technology